Transient Carbon Reserves in Barley: Malate, Sucrose and Starch Are the Main Players, Their Quantitative Involvement Being Light Intensity Dependant - Barros, Kallyne A.; Esteves-Ferreira, Alberto A.; Inaba, Masami; Meally, Helena; Finnan, John; Barth, Susanne; Sulpice, Ronan (Frontiers in Plant Science, 2020)
Under natural environment plants experience different light intensities which can affect photosynthesis and consequently the availability of carbohydrates for daytime growth and their transient storage to supply night growth. We grew a spring barley cultivar, Propino, under three different light intensities under warm days and nights, and evaluated the spatial and diurnal adjustments occurring in the transient carbon stores. Leaves under high light at the end of the day accumulated mainly sucrose (30%) and malate (35%), with lower content of hexoses (5%), starch (15%) and fructans (15%). Under low light, plants presented reduced photosynthesis, with lower metabolite contents at end of day. The malate represented 51% of the total carbon accumulated at end of the day, at the expense of sucrose (12%), other metabolite contributions remaining similar to high light. The percentage of metabolites consumed at night was similar for all light intensities with around 75% of the sucrose and starch being mobilised whilst malate and fructans were only partially mobilised with 56 and 44%, respectively. Altogether, sucrose and malate were the main contributors of the total carbon used at night by barley plants, sucrose being predominant under high light (35% vs. 27%), but malate being the major metabolite used under low light with 40% of the total carbon consumed. Interestingly, light intensity also influenced the location of the C transient stores, the plants under low light prioritising the accumulation of the metabolites, mostly malate, in the youngest tissues. Therefore, light influences quantitatively, but also qualitatively and spatially the carbon stores in the spring barley cv. Propino, suggesting a tight regulation of the primary metabolism.